Poor's manual of the railroads of the United States - Poor, Henry V. (Henry Varnum), 1812-1905 (H.V. & H.W. Poor, 1895)
"With an appendix containing a full analysis of the debts of the United States, the several states, municipalities etc. Also statements of street railway and traction companies, industrial corporations, etc." (statement omitted on later vols.).